Compatibility and thermal stability studies on plasticized PVC/PMMA blend polymer electrolytes complexed with different lithium salts - Elizabeth,R. Nimma (2005)
The lithium salt (x) (X= LiAsF6, LiPF6, LiN(C2F5SO2)2 , LiN(CF3SO2)2, LiBF4) was complexed with a host of poly(vinyl chloride) (PVC)/ poly(methyl methacrylate) (PMMA) blend polymer and plasticized with a combination of ethylene carbonate (EC) and propylene carbonate(PC). The polymer electrolyte films were prepared for constant PVC/PMMA blend ratio. The electrochemical stability and thermal stability of the solid polymer electrolytes were reported. The role of PMMA to the phenomena occurring at the interface between the electrolyte and the lithium metal electrode was explored.